Influence of different loading levels, cutting and mixing times on total mixed ration (TMR) homogeneity in a vertical mixing wagon during distribution: a case study. Issue 1 (2nd January 2019) - Costa, Annamaria; Agazzi, Alessandro; Perricone, Vera; Savoini, Giovanni; Lazzari, Massimo; Nava, Stefano; Maria Tangorra, Francesco
Abstract: This study investigated the influence of different loading levels, cutting and mixing times on total mixed ration (TMR) homogeneity delivered along the feeding alley of dairy cows. The TMR homogeneity along the alley was investigated according to three mixing wagon loads (40, 70 and 100% of the nominal capacity), three cutting times (4, 5 and 6 min) and three mixing times (4, 5 and 6 min). The diet (70:30 forage/concentrate ratio) was supplied by a two-screws vertical mixing wagon (maximum nominal capacity, 21 m 3 ). A preliminary variance analysis of chemical parameters was performed on samples collected in the mixing wagon: samples of released TMR were taken at the beginning, in the middle and at the end of the feeding alley (50 m long). The chemical parameters of the diet revealed no significant effects on the homogeneity of the samples for cutting time ( p >.05). Mixing wagon loading affected crude protein (CP) ( p < .05) and neutral detergent fibre (NDF) content ( p < .01), while mixing time influenced dry matter (DM) of the diet ( p < .05). The loading level of the mixing wagon affected the difference of the collected samples from the formulated diet for ash content. The 70% of the nominal capacity load of the mixing wagon showed the lower difference values between expected and chemically determined NDF ( p < .01), CP ( p < .05) and ether extract (EE) ( p < .05) content in the diet. The DM and NDF differences along the alley, affected by mixing times ( p < .05), showed a poor uniformity of ingredients during distribution, although samples uniformity at wagon level. Highlights: The efficiency of a two-screw vertical mixing wagon on total mixed ratio uniformity was evaluated on diet samples delivered along the feeding alley. Three loading levels, three cutting and three mixing times were considered for the mixing wagon. Mixing wagon loading affected CP and NDF content; mixing time influenced DM and NDF content at the delivery points.